Assessment of groundwater quality by using statistical analysis from kopargaon taluka, Ahmednagar, India - A.V., Deshpande; S.N., Patil (International Journal of Advanced Geosciences, 2016)
The study was conducted to evaluate the groundwater quality along the Kopargaon taluka. Thirty six ground water samples were collected from different sources in pre monsoon and post monsoon season, during the year 2013. The descriptive statistical analysis was carried out besides Pearson correlation. Correlation analysis revealed that very strong correlation exists between HCO3and Na(0.961), HCO3and Mg++ (0.935), HCO3and EC (0.927). Where highly negative correlation is observed between Na and pH (-0.537) during pre-monsoon season. During post monsoon season highly positive correlation is observed between Cl- and Ca++ (0.973), Ca and EC (0.967), Cl- and EC (0.966), SO4 and EC (0.948). Where, highly negative correlation is observed between Ca and pH (-0.533).